Employee productivity, employment growth, and the cross-border acquisitions by emerging market firms - Ataullah, Ali; Le, Hang; Sahota, Amandeep S. (Wiley, 2014)
We examine the impact of the cross‐border acquisitions made by firms from emerging markets on employee productivity and employment growth. The literature suggests that cross‐border acquisitions enable emerging market firms to obtain new skills and knowledge‐intensive assets, which, in turn, may increase productivity. However, our empirical analysis suggests that cross‐border acquisitions reduce employee productivity and have a limited impact on employment growth. Moreover, we find that cross‐border acquisitions in less‐developed countries and in culturally distinct countries reduce productivity. Overall, our findings cast doubt on the idea that cross‐border acquisitions enable emerging market firms to improve the productivity of one of their most important resources—namely, their human capital.